2016
DOI: 10.3389/fpsyt.2015.00189
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Consequences of Chronic Drug Use: Relevance to Treatment Approaches

Abstract: Heavy use of drugs impacts of the daily activities of individuals in these activities. Several groups of investigators have indeed documented changes in cognitive performance by individuals who have a long history of chronic drug use. In the case of marijuana, a wealth of information suggests that heavy long-term use of the drug may have neurobehavioral consequences in some individuals. In humans, heavy cocaine use is accompanied by neuropathological changes that might serve as substrates for cognitive dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 136 publications
0
56
0
3
Order By: Relevance
“…The longitudinal ABCD study could determine the direction of effect between cognition and substance use/disorders, and if specific substances influence particular aspects of cognition by affecting specific areas of the developing brain. However, regardless of direction, poorer cognitive functioning negatively impacts daily life [4,5] and may cause lack of insight into one’s substance use as a source of problems, impeding treatment utilization [80,81] or decreasing the likelihood of effective treatment [1,3]. While abstinence or reduced substance use may partially improve cognition [69,82], future research should determine whether factors shown to protect against cognitive impairments in aging adults, e.g., healthy diet [83,84], physical activity [85], and intellectual activities [86], also protect against cognitive impairments in populations with difficulties in reducing substance use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The longitudinal ABCD study could determine the direction of effect between cognition and substance use/disorders, and if specific substances influence particular aspects of cognition by affecting specific areas of the developing brain. However, regardless of direction, poorer cognitive functioning negatively impacts daily life [4,5] and may cause lack of insight into one’s substance use as a source of problems, impeding treatment utilization [80,81] or decreasing the likelihood of effective treatment [1,3]. While abstinence or reduced substance use may partially improve cognition [69,82], future research should determine whether factors shown to protect against cognitive impairments in aging adults, e.g., healthy diet [83,84], physical activity [85], and intellectual activities [86], also protect against cognitive impairments in populations with difficulties in reducing substance use.…”
Section: Discussionmentioning
confidence: 99%
“…NESARC-III included 12 items from the Strategic Planning and Organization EFI sub-scales to provide brief assessment of domains with widely-established impairments among patients in treatment for substance use [3,6,7]. These subscales previously evidenced good reliability (α=.70 and .75, respectively [44]), and correlated as predicted to demographic characteristics, other cognitive measures, and psychological attributes [44,50,51].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ultimately contributes to maintaining continuous drug-seeking behaviors (Cadet and Bisagno 2015), and thus indirectly enhances all of the toxicological effects of METH abuse. METH is often consumed for its effects which, among others, include increased energy levels and decreases in fatigue, increased psychomotor activity and alertness, anorectic effects, increases in sex drive, and euphoria.…”
mentioning
confidence: 99%
“…METH is often consumed for its effects which, among others, include increased energy levels and decreases in fatigue, increased psychomotor activity and alertness, anorectic effects, increases in sex drive, and euphoria. Yet, irritability, agitation, risky sexual behaviors, (motor) stereotypies, psychosis, seizures, hyperthermia and other systemic effects are also common acute (side) effects of METH consumption (Panenka et al 2013;Cadet and Bisagno 2015;Chomchai and Chomchai 2015). Those effects are mainly attributed to increases in both central and peripheral monoaminergic signaling, with strong effects in the noradrenergic (NA) and dopaminergic (DA) systems (5-HT) (Schep et al 2010;Carvalho et al 2012).…”
mentioning
confidence: 99%